PENGGUNAAN RUMUS STIRLING DAN FUNGSI PEMBANGKIT MOMEN PADA PROSES PEMBUKTIAN DISTRIBUSI NORMAL SEBAGAI PENDEKATAN DISTRIBUSI BINOMIAL - Santosa, Raden Gunawan; Haryono, Nugroho Agus (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN (EPSILON: JOURNAL OF PURE AND APPLIED MATHEMATICS), 2024)
Research in mathematics and statistics can be categorized into two main types: analytical-theoretical research and applied-practical research, both of which make significant contributions to statistical analysis. This research is particularly relevant to the analysis of large-scale binary variables, where the binomial distribution is often used as the basis for computation. In such cases, the normal distribution can serve as an approximation to the binomial distribution, reducing the complexity of calculations. This study aims to demonstrate that the normal distribution can be used as an approximation for the binomial distribution. Two proof methods are presented: one utilizing the moment-generating function and the other employing Stirling's formula. The methodology involves a literature review by gathering and analyzing various relevant references. The findings indicate that as the value of ???? n increases, the difference between calculations using the binomial and normal distributions approaches zero exponentially.